Intervención del Trabajador Social en el proceso de gestión humana y la medición del clima organizacional (Revista de la Facultad de Trabajo Social, 2020)
The problems and needs that are affecting organizations are the new scenarios for training and professional intervention. Therefore, it is imperative for us to know and beat them. More than ever before, it is now urgent to reconsider what we are and what we want to be, having an education focus that links us to knowledge and creativity. This is why it is needed to have the professional Social Worker involved in the organization since it favors social and work well being promoting changes that regulate the running of organizations, searching for a sense of commitment and belonging towards the company and at the same time, contributing to its higher level of work satisfaction, benefiting an organizational atmosphere which is favorable for productivity, effectiveness, efficacy and quality of their services.
Keywords: human magnagement; organizational climate; social worker; job satisfaction